2009
DOI: 10.4103/0256-4947.57167
|View full text |Cite
|
Sign up to set email alerts
|

Renal biopsy in patients with type 2 diabetes mellitus: indications and nature of the lesions

Abstract: BACKGROUND AND OBJECTIVES:The prevalence of non diabetic renal disease (NDRD) among patients with type 2 diabetes mellitus varies widely depending on the selection criteria and the populations being studied. The aim of this study was to evaluate the renal biopsies performed on type 2 diabetic patients for suspicion of NDRD and to correlate the pathological with the clinical and laboratory findings.SUBJECTS AND METHODS:We selected and reviewed biopsies performed on type 2 diabetics for clinically suspected NDRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 19 publications
(11 reference statements)
6
40
1
Order By: Relevance
“…The high prevalence of IgA nephropathy was in accordance with findings from the aforementioned literature review, which showed prevalence rates ranging from 7.1% to 44.8% [10,15,16,21,28,30]. The disease spectrum of DN complicating NDRD in China might be thought to be different from that in other parts of the world.…”
Section: Discussionsupporting
confidence: 85%
“…The high prevalence of IgA nephropathy was in accordance with findings from the aforementioned literature review, which showed prevalence rates ranging from 7.1% to 44.8% [10,15,16,21,28,30]. The disease spectrum of DN complicating NDRD in China might be thought to be different from that in other parts of the world.…”
Section: Discussionsupporting
confidence: 85%
“…[2] A recent study from Taiwan observed AKI(58.8%) in majority of patients while in Kuwait, it was hematuria. [1426] From these review of literatures, it is obvious that presenting syndrome can be different.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Thailand showed MN as commonest NDRD, while in Kuwait, it was CresGN. [2629] Conversely, Shan and Pham reported FSGS as the most common NDRD. [1517] These results suggest that prevalence of different category of biopsy-proven renal disease in diabetic patients depends on the usual prevalence of renal disease in the total population according to the geographical area and ethnic characteristics and NDRD is merely a coincidental in type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrologists are sometimes reluctant to perform a renal biopsy on patients with DM because of the potential risks of the procedure such as hematuria, perirenal hematoma, arterial embolization, and even the necessity for a nephrectomy [10]. Moreover, there exist some contraindications for renal biopsy such as the solitary kidney and cortical atrophy [11]. Additionally, many primary hospitals are at present unable to perform the renal biopsy.…”
Section: Introductionmentioning
confidence: 99%